Association of left ventricular late gadolinium enhancement with left atrial low voltage areas in patients with atrial fibrillation. Issue 10 (6th February 2018) - Stegmann, Clara; Jahnke, Cosima; Paetsch, Ingo; Hilbert, Sebastian; Arya, Arash; Bollmann, Andreas; Hindricks, Gerhard; Sommer, Philipp
Abstract: Aims: Presence of late gadolinium enhancement (LGE) is related to adverse cardiovascular outcome. Many patients suffering from atrial fibrillation (AF) undergo cardiovascular magnetic resonance (CMR) imaging prior to ablation. Since quantification of atrial fibrosis still lacks reproducibility, we sought to investigate risk factors for the presence of left ventricular (LV)-LGE and a possible correlation between ventricular fibrosis as defined by positive LGE and pathological atrial voltage maps evaluated by 3D mapping systems. Methods and results: Between May 2015 and January 2017, 241 patients with AF (73% persistent AF, 71% male, mean age 62.8 ± 10.1 years, Redo procedure in 24%, AF history 4.5 ± 5.2 years) underwent CMR including LV LGE prior to pulmonary vein (PV) isolation at Heart Center Leipzig. Depending on CMR results, two groups were separated: 'LV-LGE negative' (Group A, n  = 197, 82%) and 'LV-LGE positive' (Group B, n  = 44, 18%). To identify low voltage areas (LVA), a 3D electro-anatomic map was created during PV isolation. Multivariate analysis revealed male gender [odds ratio (OR) 7.6, 95% confidence interval (95% CI) 2.4–23.9, P  = 0.001] and an increased CHA2 DS2 VASc Score (OR 1.6, 95% CI 1.2–2.2, P  = 0.004) as significantly associated with LV-LGE. Impaired left ventricular ejection fraction, LV dilatation, larger LA size and, enlarged septum diameter occurred significantly more often in the 'LGE positive' group. Low voltage areas were detected in 83 patients overall (34%): Group A: n  = 64/197 (33%), Group B: n  = 19/44 (43%) ( P  = 0.177). Conclusion: Male gender and high CHA2 DS2 VASc Score are significantly associated with presence of LV-LGE, but LV-LGE is not associated with left atrial LVA.